A Survey of Classification Results for Solutions to the Liouville Equation (Journal of Mathematical Study, 2024)
In this expository paper, we survey some results concerning the classification of solutions to the Liouville equation $∆u+e^{2u} =0$ in $\mathbb{R}^2.$ .
Keywords: Classification; Liouville equation.